SUSTAINABLE ISTIMA' (LISTENING) LEARNING: LEARNING INNOVATION BASED ON THE COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH - Triani (cendekia citra gemilang, 2026)
Arabic language instruction in many higher education institutions continues to rely on conventional and less innovative pedagogical approaches. Such practices often hinder students’ ability to effectively develop listening skills and to comprehend texts and contextual meanings in a comprehensive manner. The Communicative Language Teaching (CLT) approach, which emphasizes meaningful communication and the use of language in authentic contexts, is therefore considered highly relevant for enhancing students’ Istima’ (listening) proficiency.This study aims to investigate the implementation of the Communicative Language Teaching (CLT) approach in the teaching of Maharotul Istima’ at Sekolah Tinggi Islam Al Mukmin (STIM) Sukoharjo, as well as to examine its impact on students’ engagement, listening comprehension, and self-confidence. Employing a qualitative approach with a case study design, data were collected through classroom observations, in-depth interviews, and documentation of instructional materials and recorded learning activities. The findings reveal that the implementation of CLT significantly promotes students’ active participation in communicative listening and speaking practices. Instructional strategies such as listening-focused tasks, group discussions, role-play, and spontaneous question-and-answer sessions were found to enhance student engagement, improve speaking confidence, and increase learning motivation. Despite several identified challenges, including the rapid pace of audio materials, students’ reluctance to participate verbally, disparities in proficiency levels, time constraints, and limited instructional facilities, the overall application of CLT demonstrates a positive impact on both the cognitive and affective domains of learning. Therefore, it is recommended that instructors adopt gradual material adaptation, provide intensive support for lower-proficiency learners, and foster an inclusive and supportive learning environment to optimize instructional outcomes